滚动轴承扩展寿命计算方法及影响因素研究 - 王征兵; 刘忠明 (Jixie chuandong)
Calculation methods of rolling bearings fatigue life and their characteristics are introduced.Based on ISO281:2007,calculation method of life modified coefficient is described in detail.Combined with an example of rolling bearing life calculation,some factors affecting bearing life are analyzed.